Role of intraoperative patients positioning in endoscopic full-thickness resection of large gastric tumors under general anesthesia - Zhou, Li-Jun; Xing, Fei; Chen, Dan; Li, Yan-Na; Rafiq, Shoaib Mohammad (Frontiers in Oncology, 2022)
Full thickness endoscopic resection of large submucosal gastric tumors (>3 cm) is a big challenge for endoscopists. Issues include how to efficiently resect the lesion, obtain homeostasis, and suture the defect. There are no guidelines regarding the importance of patient position on the success of endoscopic resections in anesthetized patients. Typically, the patient is placed in left lateral position for the endoscopic therapy and during the procedure patient’s position is changed to maintain the tumor above the gastric fluids to prevent gastric juices and tumor or tumor fragments from falling into the peritoneal cavity in the event of perforation. This study emphasized the importance of planning the procedure to ensure that the patient's position and anesthetist’s concerns are met and allow optimal access to the lesion for endoscopic resection. Prior to sedation the patient should be positioned so that the tumor is in the up position which also prevents blood obscuring the operative field, helps detect bleeding points for immediately hemostasis. In addition, due to gravitational effect, the resected tumor will fall into the gastric cavity exposing the root of the tumor making resection easier and reduce procedure time. Preplanning avoids unnecessary readjustment of positioning and improves the ease and safety of the procedure.